From Ascetic Ideals to Honest Illusions: A Nietzschean Interpretation of Inception - Yonghwa Lee; Kyoung-Min Han (Film-Philosophy)
This article illuminates the open ending of Christopher Nolan's film Inception (2010) in light of Friedrich Nietzsche's philosophy. Drawing particularly on Nietzsche's notions of ascetic ideals and honest illusions, the article contends that Cobb's refusal to look at the spinning top can be seen not necessarily as his renunciation of autonomy but as his new attempt to affirm his existence and create meanings. Mal's tragic death has turned Cobb into an ascetic idealist who paradoxically resorts to self-torture to alleviate his pain and suffering. Only when he sees the destructive power of his sense of guilt about Mal does he come to realize that what he really needs is not exactly the ability to distinguish the dream world from reality per se but the ability to make things seem and feel real – that is, in Nietzsche's words, honest illusions. Faced with the challenge to regain the capability to see and appreciate illusions as illusions without deceiving himself into believing that they are real, Cobb takes “a leap of faith” with Saito into the world to which he wishes to belong and finally embraces the moment of seeing his children's faces, which, fortunately for him, seem real – that is, “good” – enough.